2018
DOI: 10.1101/285122
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Holocene DNA sequences – a dream come true

Abstract: Microscopic marine planktons have played a major role in the Earth's ecosystem and accounts for half the globe's primary production. Predicting the fate of marine planktons is imperative to understanding how ocean life will change in future centuries and how organisms have adapted to changes in the past over long timescales (over thousands of years). Studies of revived resting spores of marine diatoms will serve as excellent proxies of environmental change in marine environments. Thus far, only about a century… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Resting cells and spores are also resistant to dark, cold and nutrient limited conditions (McQuoid & Hobson, 1995). According to Sanyal et al (2019), resting spores of diatoms can survive for centuries in nature and the diatoms spores are still viable if the perfect conditions are given. The present results showed that the germination period for most of the species exposed to desiccation can occur within a short period, mostly after 72 hours after return of natural conditions, which coincide with Sanyal et al (2019).…”
Section: Discussionmentioning
confidence: 99%
“…Resting cells and spores are also resistant to dark, cold and nutrient limited conditions (McQuoid & Hobson, 1995). According to Sanyal et al (2019), resting spores of diatoms can survive for centuries in nature and the diatoms spores are still viable if the perfect conditions are given. The present results showed that the germination period for most of the species exposed to desiccation can occur within a short period, mostly after 72 hours after return of natural conditions, which coincide with Sanyal et al (2019).…”
Section: Discussionmentioning
confidence: 99%
“…Some of these dormant propagules can be stored and accumulate in the environment. In marine sediments, resting stages are observed for marine ciliates (Verni and Rosati 2011), sponges (Simpson and Fell 1974), jellyfish (Kawahara et al 2013), zooplankton (Radzikowski 2013), and many taxa comprised of phytoplankton such as cyanobacteria (Perez et al 2017), diatoms (McQuoid et al 2002, Sanyal et al 2019, dinoflagellates (Anderson andRengefors 2006, Ellegaard and, prasinophytes, and haptophytes (Ellegaard et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Marine propagules can be used to determine the effect of environmental changes on marine ecosystems (Dale et al 1999, Brede et al 2009, Harnstrom et al 2011. For instance, the research field of resurrection ecology is based on the revival of organisms in dormant stages that can remain viable for long periods in soils, sediments, ice, and permafrost (Angeler 2007, Orsini et al 2013, Radzikowski 2013, Houwenhuyse et al 2018, Sanyal et al 2019. The term revival is used to designate the germination of seeds, spores, or cysts and/or the hatching of eggs of metazoans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation